Novel Coconut Vinegar Attenuates Hepatic and Vascular Oxidative Stress in Rats Fed a High-Cholesterol Diet - Malakul, Wachirawadee; Seenak, Porrnthanate; Jumroon, Noppadon; Arikit, Siwaret; Kumphune, Sarawut; Nernpermpisooth, Nitirut (Frontiers in Nutrition, 2022)
Background Hypercholesterolemia is an independent modifiable risk factor that accelerates the development of both non-alcoholic fatty liver and atherosclerosis. Coconut water contains a variety of phytochemicals that make it appealing for producing vinegar. Coconut vinegar is rapidly gaining popular for health benefits in Southeast Asia. The purpose of this study is to evaluate the effect of daily supplementation of coconut vinegar on hepatic and vascular oxidative stress in rats fed a high-cholesterol diet (HCD). Methods Mature coconut water was fermented with coconut sap sugar using Saccharomyces cerevisiae, and Acetobacter aceti vat Europeans, respectively. Bioactive compounds and antioxidant capacity of coconut vinegar were examined in in vitro. Adult male Sprague-Dawley rats were randomly divided into four groups; the control group fed a standard diet (S), the group received HCD (SC), the group received HCD supplemented with coconut vinegar at a dose of 1 mL/kg/day (SCV), and the group received HCD with atorvastatin at a dose of 30 mg/kg/day (SCA). After 8 weeks, serum metabolic profiles, fatty liver, hepatic and vascular oxidative stress were determined. Results In in vitro studies, coconut vinegar was rich in phenolic compounds and organic acids. The antioxidant capacity of 30 μL of coconut vinegar was 181.55± 8.15 μM Trolox equivalent antioxidant capacity (TEAC). In the HCD fed rats, daily supplementation of coconut vinegar reduced weight gain, serum triglycerides, and fasting blood sugar levels without renal or liver toxicity. In the liver, coconut vinegar reduced accumulation of both hepatic cholesterol and hepatic triglyceride, and it also reduced hepatic 4-Hydroxynonenal (4-HNE) lipid peroxidation. In the aortic tissues, coconut vinegar increased nitric oxide bioavailability and reduced aortic 4-HNE lipid peroxidation. Conclusion Novel coconut vinegar is the source of antioxidants, and daily supplementation of coconut vinegar was found to attenuate dyslipidemia-induced hepatic and vascular oxidative stress by protective against cellular lipid peroxidation.